Political Connections and Firms : Network Dimensions - Bussolo, Maurizio (World Bank, Washington, DC, 2018)
Business and politicians' interaction is pervasive but has mostly been analyzed with a binary approach, i.e. either a firm is connected to a politician or not. Yet the network dimensions of such connections are ubiquitous. This paper uses use a unique data set for seven economies that documents politically exposed persons and their links to companies, political parties, and other individuals. The data set is used to identify networks of connections, including their scale and composition. The analysis finds that all country networks are integrated having a Big Island. They also tend to be marked by small-world properties of high clustering and short path length. Matching the data to firm-level information, the paper examines the association between being connected and firm-level attributes. The originality of the analysis is to identify how location in a network, including the extent of ties and centrality, is correlated with firm scale and performance. In a binary approach, such network characteristics are omitted and the scale and economic impact of politically connected business may be significantly mis/under-estimated. By comparing the results of the binary approach with the network approach, the paper also assesses the biases that result from ignoring network attributes.